New Zealand University students' knowledge of fertility decline in women via natural pregnancy and assisted reproductive technologies. (3rd July 2015) - Lucas, Nathanael; Rosario, Roseanne; Shelling, Andrew
Abstract: Female fertility declines with age. University students are the group of people most likely to postpone parenthood, yet several international studies have shown that they overestimate their fertility. We designed a questionnaire based on a previous study in Israel, where university students were asked to answer questions related to their awareness of fertility decline in spontaneous and in vitro fertilisation (IVF) pregnancies, and methods they considered would prolong their reproductive lifespan. Our study has shown that New Zealand University students overestimated the rates of pregnancy for both spontaneous natural and IVF pregnancies. Students are mainly aware of the availability of assisted reproductive technologies (ARTs), but overestimate their effectiveness. Few students mentioned non-medical or well-being initiatives as measures to prolong parenthood. It is important that university students are aware of the rate of fertility decline in women, as although ARTs can be effective at times, they are not a guaranteed solution to an ageing woman's fertility. New Zealand University students, like other cohorts, overestimated the chances of a woman getting pregnant and predicted the fertility decline to occur much later than it does in reality.